Community Service through Impactful Internship: Enhancing Administrative Governance and Human Resource Development in State-Owned Enterprises - Anggressya Octaviana Nur Rahayu; Hafid Aditya Pradesa; Muhammad Taufiq (TGO Journal of Community Development, 2025)
This article presents a comprehensive community service implementation contextualized through an "impactful internship" (magang berdampak) model, seamlessly integrating academic institutional contributions with industrial operational needs at PT XYZ (Persero). The program directly addresses critical organizational challenges by bridging higher education competencies with real-world administrative governance and human resource management within the enterprise's Human Capital Management Division. Utilizing a qualitative descriptive methodology structured around the Indonesian National Work Competency Standards (SKKNI) Number 109 of 2024, the community service activities encompass rigorous preparation, direct operational execution, and continuous evaluation stages. The findings demonstrate that embedding students into strategic state-owned enterprises significantly optimizes administrative workflows, digital archiving security, and the execution of vocational student management and employee training programs. Furthermore, the initiative effectively mitigates chronic administrative bottlenecks caused by high-volume workflows and strict defense-industry compliance protocols. Ultimately, this collaborative model serves as a powerful mutual catalyst, enhancing organizational efficiency and institutional capacity while fostering professional resilience, civic responsibility, and practical readiness among public administration students.